1988
DOI: 10.1002/bip.360271107
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficients of segmentally flexible macromolecules with two subunits: A study of broken rods

Abstract: SynopsisA general treatment for the solution dynamics of segmentally flexible macromolecules having two subunits is presented. Bead modeling allows for a complete inclusion of hydrodynamic interactions in this treatment. "he finite size of the beads is also considered, so that it is therefore possible to account properly for torsional motions of the subunits. Expressions for the components of the resistance matrix are derived. From them, the translational and rotational diffusion coefEcients can be calculated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Instead of the nine degrees of freedom of the swivel-jointed rod, the hinged rod has only seven, of which six are those proper for a rigid particle, and the remaining one is that corresponding to bending in the particle's plane. Mellado et al (1988) have shown that the Di, coefficient of the hinged rod is the same as that for the swiveljointed rod. However, Dout differs appreciably, and is not nearly constant as in Fig.…”
Section: In-plane Bendingmentioning
confidence: 84%
See 4 more Smart Citations
“…Instead of the nine degrees of freedom of the swivel-jointed rod, the hinged rod has only seven, of which six are those proper for a rigid particle, and the remaining one is that corresponding to bending in the particle's plane. Mellado et al (1988) have shown that the Di, coefficient of the hinged rod is the same as that for the swiveljointed rod. However, Dout differs appreciably, and is not nearly constant as in Fig.…”
Section: In-plane Bendingmentioning
confidence: 84%
“…1983;Garcia de la Torre etal. 1985;Mellado et al 1988). The Wegener treatment has been presented for the most general case of a particle with any number of segments, which must be allowed to undergo any type of internal motion• The treatment of Harvey has been presented for the particular case of two segments and one joint which can act either as a universal swivel, or as a hinge allowing only bending (in-plane flexing) but not torsions.…”
Section: Instantaneous Coefficientsmentioning
confidence: 99%
See 3 more Smart Citations